Microgrid Control Techniques: A Review - Abdulmalik Ibrahim Dano; Sabo Aliyu; Olutosin Ogunleye ; Abdul Wahab Noor Izzri; Hossein Shahinzadeh; Abdulmajid Muhammad Na’inna (Universitas Negeri Surabaya or The State University of Surabaya, 2025)
Microgrids (MGs) are localized energy systems that integrate distributed energy resources (DERs) such as renewable energy, energy storage systems (ESS), and conventional generation sources. A critical challenge in the operation of microgrids is maintaining frequency stability, particularly during transient disturbances or load imbalances. This review provides a comprehensive analysis of various frequency control strategies employed in microgrids to ensure stable and reliable operation. The paper categorizes existing approaches into primary, secondary, and tertiary frequency control methods, evaluating their mechanisms, advantages, and limitations. Primary control focuses on immediate frequency regulation through local droop control, while secondary control ensures the restoration of frequency to its nominal value through centralized or decentralized coordination. Tertiary control manages economic dispatch and energy optimization for long-term stability. Additionally, the review addresses the impact of DER characteristics, such as variability and intermittency, on frequency regulation, and discusses advanced techniques, including model predictive control, fuzzy logic control, and Neural network control. The paper concludes with a discussion on future trends in microgrid frequency control, emphasizing the need for robust encryption and intrusion detection systems that protect microgrid control networks from cyber threats, ensuring reliable frequency regulation even in the event of a cyber-attack.